Paternal race/ethnicity and risk of adverse birth outcomes in the United States, 1989-2013 - Yu Li; Zhehui Luo; Claudia Holzman; Hui Liu; Claire E. Margerison (AIMS Press, 2018)
Objectives: Investigate adverse birth outcomes in the United States (US) from 1989-2013 in relation to paternal and maternal race/ethnicity. Design: We used US natality data for singleton births to women 15-44 with information on birthweight, gestational age, and covariates (n = 90,771,339). We calculated unadjusted and adjusted probabilities of preterm birth (PTB, < 37 weeks gestation) and small for gestational age (SGA, < 10th percentile) among all combinations of maternal and paternal race/ethnicity: non-Hispanic black (NHB), non-Hispanic white (NHW), Hispanic, and Asian, and where paternal race/ethnicity was missing. Results: Missing, followed by NHB, paternal race/ethnicity had the two highest risks of PTB within each maternal racial/ethnic group. Asian, followed by NHW, paternal race/ethnicity had the two lowest risks of PTB. For SGA, however, Asian, followed by missing, paternal race/ethnicity had the two highest risks, and NHW race/ethnicity had the lowest risk. Our findings also demonstrate effect modification on the additive scale, with missing and NHB paternal race/ethnicity conferring a larger increase in risk of PTB for NHB women compared to women of other race/ethnicity groups. Conclusions: These data confirm US disparities in adverse birth outcomes by maternal and paternal race/ethnicity and argue for increased resources and interventions in response.